أثر جائحة كورونا والأوضاع المتشابهة على المدد والمواعيد الإجرائية - أحمد, د.عطا عبدالحكيم (Sulaimani Journal for Humanities, 2023)
The spread of the Corona virus in Iraq and the Kurdistan Region resulted in the impossibility of litigants in civil lawsuits to perform their duties and exercise their procedural rights under legal deadlines and periods, that’s either because of the suspension of official working hours in judicial institutions and other state institutions, or because they were infected with the virus after the end of the suspension period and during working hours.And if each of the statement released by the Judicial Council in Iraq and the region has saved the litigants from imposing the procedural penalty on them for not doing what is required because of the suspension, as it was stated in each of the mentioned statements to stop the legal periods in effect throughout the period of suspension.But what for the case in which one of the litigants is infected with the virus? Or exposed to any epidemic or other circumstance similar to it in terms of effect.Are there provisions in the Civil Procedure Code and the complementary laws that aid litigants and prevent the imposition of procedural penalties on them, or there is a legislative shortcoming in this regard. In this research and through a comparative study, we will try to uncover these provisions and legislative shortcomings and then find appropriate solutions and make recommendations to ensure that they are addressed.